Beyond the Classroom: Sustainable Science Learning in Authentic Environments - Arcia-Hernández, Pedro; Rosales-Cevallos, Marco Mauricio; Rivera-Castañeda, Patricia Margarita; Bedoya-Ávalos, José Rolando; Pruneda-Ávila, Nancy Elizabeth; Torres-Vásquez, Jorge; Zúñiga, Juan Manuel Martínez; Casanueva-Yáñez, Galvarino (Journal of Ecohumanism, 2024)
The objective of this paper is to study sustainable science learning in authentic environments, based on the perceptions of school-level teachers. The study follows a quantitative approach, supported by the positivist paradigm, for which data was collected using a dichotomous questionnaire applied to 42 teachers from various countries. The conceptual topics underpinning this work include (a) sustainable learning, (b) science teaching, and (c) authentic environments. Among the main results, it was found that transcending the traditional approach to science teaching facilitates the conversion of the abstract language of science into simpler and more easily understandable terms for students through didactic methodologies where practice is more fundamental than memorization. In this regard, it was concluded that when the traditional classroom approach is replaced by an innovative one, where the natural environment, daily practice, and the application of knowledge and concepts in real-life situations are the common denominators, more meaningful learning is achieved, and active participation is promoted, thus creating an authentic learning environment.